THE GREAT BOOKS : SIXTH YEAR COURSE (1957)
CONTENIDO: V. 1 AESCHYLUS: PROMETHEUS BOUND. -- PLATO: PHAEDRUS. -- ARISTOTLE: METAPHYSICS, BOOK XII. -- V. 2 LONGINUS: ON THE SUBLIME. -- ST AUGUSTINE: ON NATURE AND GRACE ON GRACE AND FREE WILL. -- ST THOMAS AQUINAS: THE EXISTENCE AND SIMPLICITY OF GOD. -- V. 3 CHAUCER: CANTERBURY TALES. -- SHAKESPEARE: RICHARD II. -- V. 4 CERVANTES: DON QUIXOTE. --V. 5 SPINOZA: ETHICS. -- HUME: DIALOGUES CONCERNING NATURAL RELIGION. -- V. 6 VOLTAIRE: PHILOSOPHICAL DICTIONARY. -- HEGEL: PHILOSOPHY OF HISTORY. -- V. 7 DARWIN: THE ORIGIN OFSPECIES. -- V. 8 MELVILLE: BILLY BUDD, FORETOPMAN. -- HENRY JAMES: THE TURN OF THE SCREW